Zakat Sebagai Pilar Utama Pemaknaan Keadilan Sosial - Imam Baihaqi (El-Jizya: Jurnal Ekonomi Islam)
This article raises the theme of Zakat as the Main Pillar of Meaning of Social Justice using descriptive qualitative research methods. This research describes the concept of zakat in Islam, social justice in Islam, and the role of zakat as a tool for interpreting social justice. Research findings show that social justice is the main foundation in various legal and economic systems in many countries. The principle of zakat in Islam appears as a key element to achieve this goal. Zakat, as an obligation of Muslims, is not only a social charity, but is also integral to the Islamic economic system to create a fairer distribution of wealth. The importance of zakat is not limited to Muslim communities, but has universal relevance. Concepts such as social solidarity and collective responsibility for the common welfare that underlie zakat can be an inspiration for achieving social justice in various communities and nations. Involving the community in the principles of zakat is expected to create an environment where wealth and resources are distributed more evenly, giving all individuals better access to reach their full potential. Thus, zakat is not only a religious obligation, but also an important instrument for achieving common goals in realizing social justice throughout the world.